Exploring the prevalence and chest CT predictors of Long COVID in children: a comprehensive study from Shanghai and Linyi - Yin, Yong; Yang, Guijun; Wang, Na; Zeng, Mei; Jiang, Hejun; Yuan, Shuhua; Wu, Jinhong; Zhang, Jing; Cui, Juan; Zhou, Guifang; Yang, Xin; Zhang, Yunqin; et al. (Frontiers in Pediatrics, 2024)
COVID-19 constitutes a pandemic of significant detriment to human health. This study aimedaims to investigate the prevalence of Long COVID following SARS-CoV-2 infection, analyze the potential predictors of chest CT for the development of Long COVID in children. A cohort of 416 children who visited the respiratory outpatient clinics at Shanghai Children's Medical Center or Linyi Maternal and Child HealthCare Hospital from December 2022 to February 2023 and underwent chest CT scans within 1 week was followed up. Data on clinical characteristics, Long COVID symptoms, and chest CT manifestations were collected and analyzed. Multivariate logistic regression models and decision tree models were employed to identify factors associated with Long COVID. A total of 416 children were included in the study. Among 277 children who completed the follow-up, the